Climate change and heritage tourism: threats to Makgabeng in a regional context, Limpopo South Africa - Mcpherson, Fazlin Ahdielah (My University, 2020)
The Makgabeng area is situated in the north-west corner of the Limpopo province in South Africa. The Makgabeng area is an emerging tourist destination with a variety of activities to offer. The area is rich in ancient rock art sites and, as a result, has great potential for the development of heritage tourism. Extensive research has been conducted on the rock art in this region. However, the impact of climate change on heritage tourism has not yet been explored. The local community of the Makgabeng area is developing a heritage tourism destination within the region and it is important to determine whether the initiative will be sustainable, especially in the context of climate change threats to the region. In a region such as Makgabeng where the primary attraction is natural heritage tourism rather than cultural, this then poses a severe threat to tourism within the region, especially since most of these attractions are outdoors. Hence, this research project is primarily aimed at determining climate change threats to heritage tourism in the Makgabeng region, South Africa. The research has employed a mixed-method approach consisting of interviews done with various stakeholders within the tourism industry and community members in the Makgabeng region. The other methods used are hard-copy and online questionnaires, TripAdvisor reviews, and the Tourism Climatic Index (TCI). What the research has found is that people do not know that Makgabeng exists, and for those who are aware of its existence they have never visited the region. this is because the area is not being marketed effectively. The TCI scores show that winter is the best time of the year for tourism. Consequently, stakeholders and community members should market the area with this in mind. However, tourists have said they enjoy the weather in the region all year round.
A dissertation submitted n the fulfilment of the requirements for the degree of Master of Science to the Faculty of Sciences, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2020
Keywords: Rock paintings-South Africa; Heritage tourism